2015
DOI: 10.1371/journal.pgen.1005612
|View full text |Cite
|
Sign up to set email alerts
|

Protein Homeostasis Imposes a Barrier on Functional Integration of Horizontally Transferred Genes in Bacteria

Abstract: Horizontal gene transfer (HGT) plays a central role in bacterial evolution, yet the molecular and cellular constraints on functional integration of the foreign genes are poorly understood. Here we performed inter-species replacement of the chromosomal folA gene, encoding an essential metabolic enzyme dihydrofolate reductase (DHFR), with orthologs from 35 other mesophilic bacteria. The orthologous inter-species replacements caused a marked drop (in the range 10–90%) in bacterial growth rate despite the fact tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
96
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 59 publications
6
96
1
Order By: Relevance
“…Fitting the data points with Eq. 1 resulted in an excellent quantitative prediction of fitness, in agreement with recent work (20). The parameter B resulting from the nonlinear fit of Eq.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Fitting the data points with Eq. 1 resulted in an excellent quantitative prediction of fitness, in agreement with recent work (20). The parameter B resulting from the nonlinear fit of Eq.…”
Section: Resultssupporting
confidence: 89%
“…A set of points obtained for untransformed parent E. coli strain MG1655, expressing solely its WT chromosomal DHFR, grown at different TMP concentrations shows a good superimposition as well [with slight deviation at higher fitness probably due to activation of the DHFR promoter through a feedback loop (23,24)]. Also included for comparison are the data points obtained in previous studies using chromosomal orthologous DHFR replacements (20) and an IPTG-inducible promoter-controlled chromosomal DHFR expression system (13). Fitting the data points with Eq.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The folA gene is involved in encoding dihydrofolate reductase (DHFR), which catalyses an electron-transfer reaction to form tetrahydrofolate, a carrier of single-carbon functional groups utilized in central metabolism, including de novo purine biosynthesis, dTTP formation, and methionine and glycine production [21]; folA-lacking bacteria will use flavin-dependent thymidylate synthases for deoxythymidine-5'-monophosphate synthesis [22].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that as the number of nodes connecting an extant protein within its protein-protein interaction network increases, the capacity to replace that protein with another homolog decreases despite the presumed functional equivalence between the endogenous gene and the homolog (Jain et al 1999). Several orthologous protein substitution experiments demonstrated successful transfer of an alien gene to a foreign genome (Bershtein et al 2015;LariosSanz and Travisano 2009;Lind et al 2010), resulting in a fitness decrease similar to our approach, which was referred to as the "weak link approach" (Counago et al 2006). After evolving these organisms under laboratory conditions, it was demonstrated that direct accumulation of convergent mutations on the extant alien gene exhibits adaptive behavior (Counago et al 2006;Miller et al 2010;Pena et al 2010).…”
Section: Discussionmentioning
confidence: 99%